Metamorphic evolution of the North Delhi Fold Belt, implications on Delhi orogeny and the Rodinia connection. Issue 9 (5th May 2022) - Naik, Aditya; Pant, Naresh Chandra; Sharma, Jeev Jatan; Bhandari, Anubha; Sorcar, Nilanjana
Abstract : Medium‐grade metamorphic rocks representing metapelites, calc‐silicates and metavolcanics constitute the rocks of Alwar and Khetri sub‐basins of the North Delhi Fold Belt (NDFB) in southern Haryana and adjacent western Rajasthan. Using modern petrological tools including pseudosection modelling, we describe the metamorphism of the rocks representing these two sub‐basins and show that the reported westward increasing grade of metamorphism in NDFB is non‐tenable. We show that, if anything, the grade of metamorphism decreases from the central Alwar sub‐basin to the western Khetri sub‐basin. Clockwise segments of P‐T paths are constructed using effective bulk controlled pseudosections from these two sub‐basins allowing inference of a schematic P‐T‐t path for the NDFB after integration of the reported and new age data. A subduction setting for this orogeny is indicated. Published data from the South Delhi Fold Belt (SDFB) corroborate the same‐age orogeny for both segments of the Delhi Fold Belt. The previously proposed continuation of the Delhi Fold Belt suture with the Central Indian Tectonic Zone is supported by the present work. Abstract : Clockwise P‐T‐t paths for Khetri (westernmost; marked by red rectangle) and Alwar sub‐basins (eastern; marked by black rectangle) indicating a Grenvillian age (~1.1–0.9 Ga) orogeny were identified from the North Delhi Fold Belt. The prograde path is inferred to be high‐pressure type.